2016
DOI: 10.1186/s13731-016-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Resources, experience, and perseverance in entrepreneurs’ perceived likelihood of success in an emerging economy

Abstract: This paper introduces new results obtained from a statistical investigation into a 3071-observation data set collected from a Vietnamese nationwide entrepreneurship survey. From established relationships, such factors as preparedness, financial resources, and participation in social networks are confirmed to have significant effects on entrepreneurial decisions. Entrepreneurs, both financially constrained and unconstrained, who have a business plan tend to start their entrepreneurial ventures earlier. Also, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
(59 reference statements)
0
19
0
2
Order By: Relevance
“…In addition, public equity finance can be an important source for financing innovation, in similar way to how Bottazzi and Da Rin (2002) see the role of venture capital in Europe for financing credit-constrained innovative companies. Bottazzi and Da Rin (2002) show that sales growth has influence on firms' operational scales and the potential venture-capital financing prospects for young firms seeking finance, i.e., their capital structure; the view is in part supported by evidence from developed economies (e.g., Bernstein, 2015;Inkinen, 2015;Pahnke et al, 2015) as well as from developing economies (Iturrioz et al, 2015;Vuong et al, 2016a).…”
Section: A Brief Review Of the Extant World Literaturementioning
confidence: 93%
“…In addition, public equity finance can be an important source for financing innovation, in similar way to how Bottazzi and Da Rin (2002) see the role of venture capital in Europe for financing credit-constrained innovative companies. Bottazzi and Da Rin (2002) show that sales growth has influence on firms' operational scales and the potential venture-capital financing prospects for young firms seeking finance, i.e., their capital structure; the view is in part supported by evidence from developed economies (e.g., Bernstein, 2015;Inkinen, 2015;Pahnke et al, 2015) as well as from developing economies (Iturrioz et al, 2015;Vuong et al, 2016a).…”
Section: A Brief Review Of the Extant World Literaturementioning
confidence: 93%
“…The IUP Journal of Entrepreneurship Development Non-ISI, non-Scopus 2016 [5] SpringerPlus ISI Q1, Scopus Q1 2016 [6] Journal Những yếu tố kỹ thuật và nội dung lôi cuốn tác giả, và khiến cho tác giả tin vào chất lượng sản phẩm, có thể không phải là yếu tố hấp dẫn người đọc, cũng không quyết định đối với sự tác động của tác phẩm đối với cách đánh giá của độc giả.…”
Section: Ref Tạp Chí Ghi Chú 2009 [4]unclassified
“…hai bài trên hai tạp chí có ban biên tập mạnh, tên tuổi nhà xuất bản lớn (Springer Nature), và thậm chí có thứ hạng cao như SpringerPlus (thuộc Q1 của cả ISI Web of Science và Scopus).Thứ hai, bài[4] không có số liệu sâu, không có phương pháp đặc sắc, cũng không có kết quả gì gây ngạc nhiên, lại có sức gây chú ý và được sử dụng lại, và được trích dẫn nhiều hơn hẳn so với[5,6].Thứ ba, trong số hai nghiên cứu[5,6] đều do hai tạp chí của cùng nhà xuất bản là Springer Nature ấn hành, thì [6] mạnh hơn hẳn [5] về mức độ đọc (theo số liệu cung cấp của chính các ấn phẩm), và về trích dẫn. Trong khi đó, về phẩm cấp thì [5] trên tạp chí SpringerPlus đã được chỉ mục hóa trong Scopus và ISI Web of Science, với thứ hạng là Q1 và được đánh giá cao hơn hẳn [6] (Journal of Innovation and Entrepreneurship).…”
unclassified
“…Computational entrepreneurship allows the accessibility to more information and data, and consequently, leading to a more complex calculation. For instance, research has shown that entrepreneurs tend to prolong their ventures if the possibility of the first success is uncertain, while if the success chance is high, entrepreneurs are more likely to proceed with the plan (Vuong, Do, & Vuong, 2016). Connectivity and computational power help reducing the uncertainty by the thorough analysis of data and information.…”
Section: Computational Entrepreneurship: a Modus Operandimentioning
confidence: 99%